2021
DOI: 10.1186/s13059-021-02366-3
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and transcriptomic analyses reveal two-staged chloroplast biogenesis underpinning photosynthesis build-up in the wheat leaf

Abstract: Background The developmental gradient in monocot leaves has been exploited to uncover leaf developmental gene expression programs and chloroplast biogenesis processes. However, the relationship between the two is barely understood, which limits the value of transcriptome data to understand the process of chloroplast development. Results Taking advantage of the developmental gradient in the bread wheat leaf, we provide a simultaneous quantitative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 72 publications
2
31
3
Order By: Relevance
“…The role of this gene has not been explored beyond fruits of tomato and pepper. Loudya et al (2021) recently demonstrated that chloroplast proliferation, build-up of chloroplast protein import and increases in chloroplast genetic machinery (genome replication, transcription and translation) can all be completed before greening of the chloroplast. Therefore, apart from the individual candidate genes mentioned earlier it should be noted that identifying regulators that act before greening (during the first 'plastid' or 'structural establishment' phase) is fundamental to complete our understanding of chloroplast development.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
See 4 more Smart Citations
“…The role of this gene has not been explored beyond fruits of tomato and pepper. Loudya et al (2021) recently demonstrated that chloroplast proliferation, build-up of chloroplast protein import and increases in chloroplast genetic machinery (genome replication, transcription and translation) can all be completed before greening of the chloroplast. Therefore, apart from the individual candidate genes mentioned earlier it should be noted that identifying regulators that act before greening (during the first 'plastid' or 'structural establishment' phase) is fundamental to complete our understanding of chloroplast development.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…The fully formed thylakoid membrane therefore contains proteins and pigment–protein complexes including Photosystem II, the cytochrome b 6 f complex, Photosystem I and the adenosine triphosphate (ATP) synthase (Staehelin & DeWit, 1984). Whether from etioplasts in dark‐grown cotyledon cells (Pipitone et al ., 2021) or from proplastids in meristematic cells (Loudya et al ., 2021), two stages of chloroplast biogenesis can be identified: the first has been referred to as the ‘plastid phase’, or photosynthesis‐enabling ‘structural establishment phase’, while the second is the ‘chloroplast’ or ‘greening phase’, and during deetiolation this is also the ‘chloroplast proliferation phase’.…”
Section: Chloroplast Biogenesis and Division In Green Tissuesmentioning
confidence: 99%
See 3 more Smart Citations